Evaluation of the antioxidative and hypo-cholesterolemic effects of lingzhi or reishi medicinal mushroom, Ganoderma lucidum (Agaricomycetes), in ameliorating cardiovascular disease - Rahman, Mohammad Azizur; Abdullah, Noorlidah; Aminudin, Norhaniza (Begell House, 2018)
Oxidative stress (OS) and hypercholesterolemia have been linked with a heightened risk of cardiovascular disease (CVD). Because of the numerous drawbacks of synthetic antioxidants and cholesterol-lowering drugs, natural antioxidative and hypocholesterolemic agents are of immense importance. This study was designed to determine both the OS-attenuating and cholesterol-lowering capacities of the hot water extract (HWE) and of five solvent-solvent- partitioned fractions of Ganoderma lucidum. In vitro antioxidative performance of G. lucidum HWE and fractions was measured through DPPH free radical scavenging, Folin-Ciocalteu assay, lipid peroxidation inhibition, and human low-density lipoprotein (LDL) oxidation inhibition. In vivo antioxidative performance of G. lucidum was assessed by measuring the plasma and liver antioxidative enzymatic activities (catalase, glutathione peroxidase, and superoxide dismutase) in G. lucidum HWE-fed rats. In the CVD tests, the HWE at 200 mg/kg b.w. lowered plasma levels of total cholesterol, triacylglycerol, and LDL cholesterol and increased high-density lipoprotein cholesterol. The current findings indicate the therapeutic potentiality of G. lucidum as an OS-attenuating and hypocholesterolemic agent en route to withstanding CVD complications.